IONOSPHERIC EFFECTS OF SOLAR FLARES AND EARTHQUAKE ACCORDING TO DOPPLER FREQUENCY SHIFT ON AN INCLINED RADIO PATH - Salikhov, N.M.; Pak, G.D. (Academic Scientific Journal of Computer Science, 2020)
The effects in the ionosphere and the fine structure of ionospheric response to the action of X-ray and ultraviolet radiation of C1.7 - M5.2 classes flares occurred during solar cycle 24 (2014–2016) have been studied. The study was carry out using method of Doppler sounding of the ionosphere on an inclined radio path with a high time resolution (sampling frequency 25 Hz), which is based on the principle of the phase locked loop (PLL). It was shown that the intensity of C3.0-class solar flares is a minimum threshold when the appearance of disturbances in the ionosphere could be detected by the Doppler frequency shift (DFS) method. Solar flares less than С3.0-class were not reflected in Doppler frequency variations. The most expressed ionospheric response, recorded in the Doppler frequencies, occurred to X-ray flares with a sharp onset, flares with a smooth increase intensity gave a much less response. An unusual effect of the appearance of high-frequency component in Doppler frequency records in the interference beat form has been detected, indicating the occurrence of ionized heterogeneities in the ionosphere during solar flares. The appearance of high frequency component on the Doppler frequency shift records was also registered during the М5.1 earthquake. The application of Doppler frequency shift method that use the PLL loop has greatly expanded the ability to record and analyze the mechanisms of appearance the ionospheric disturbances during solar flares and earthquakes.